Molecular docking and pharmacological investigations of folenolide for its analgesic, anti-inflammatory, and antipyretic applications - Ali, Faryal Liaqat; Khuda, Fazli; Khan Khalil, Atif Ali; Jan, Asif; Khan, Muhammad Asif; Nadeem, Ahmed; Rasheed, Abdur; Ali, Syed Shaukat; Ullah, Asmat (Frontiers in Pharmacology, 2025)
BackgroundFolenolide, a novel compound, was investigated for its pharmacological potential, focusing on its analgesic, anti-inflammatory, and antipyretic effects, along with its safety profile and potential molecular targets, using in vivo models and molecular docking studies.MethodsIn vivo mouse models were used to assess acute toxicity and analgesic, anti-inflammatory, and antipyretic activities. Molecular docking simulations were conducted against key targets, including COX-2, lipoxygenase, opioid, histamine, and tankyrase receptors, to explore their potential mechanisms of action.ResultsFolenolide showed no signs of acute toxicity. The analgesic model exhibited significant peripheral analgesia in the acetic acid-induced writhing test (31.07% and 50.13% inhibition at 3 and 6 mg/kg, respectively; p < 0.01) and potent central analgesia in the hot-plate test (maximum effect at 6 mg/kg; p < 0.0001). Formalin test results confirmed both neurogenic and inflammatory phase inhibition (69.17%–78.26%). Anti-inflammatory efficacy was marked in carrageenan-induced paw edema (84.3%–94.98% reduction), histamine-induced edema (87.29%–88.6%), and xylene-induced ear edema (6.19%–8.19% weight gain suppression) (p < 0.05). Folenolide also displayed antipyretic effects, significantly reducing the rectal temperature in yeast-induced fever models. Molecular docking revealed favorable binding affinities (ΔG ranging from −4.4 to −5.9 kJ/mol) with key targets.ConclusionFolenolide exhibits strong analgesic, anti-inflammatory, and antipyretic activities with a favorable safety profile. Its pharmacodynamic effects are supported by its molecular interactions with cyclooxygenase (COX), opioids, and histamine receptor targets. These findings highlight its potential as a promising therapeutic agent for pain, inflammation, and fever management.